Analysis of snake venom composition and antimicrobial activity. (August 2018) - Charvat, Robert A.; Strobel, Raeshelle M.; Pasternak, Megan A.; Klass, Sarah M.; Rheubert, Justin L.
Abstract: With the threat of a post-antibiotic era looming, the search for new and effective antibiotics from novel sources is imperative. Not only has crude snake venom been shown to be effective, but specific components within the venoms, such as Phospholipase A2 s and l -amino acid oxidases have been isolated and demonstrated to be effective as well. Despite numerous studies being completed on snake venoms, there is a heavy bias towards utilizing the venoms from the highly toxic Elapidae and Viperidae species. Very few studies have been conducted on the less toxic, but taxonomically more diverse, Colubridae. Furthermore, an extensive review of the literature examining the efficacy and potential specificity of these venoms has not been completed. Therefore, the aims of this study were to elucidate any similarities in snake venoms as well as investigate the efficacy of snake venom antimicrobial properties towards morphologically and metabolically diverse microbial classes and the prevalence of snake species with antimicrobial properties within each snake family. The results indicate that snake venoms and their isolated components are powerful antimicrobial agents but vary in efficacy towards different microbial classes. Furthermore, due to similarities in venom composition, and limited preliminary studies, the less toxic Colubridae family may be a fruitful area of research to find novel antimicrobial agents that are less harmful to humans. Graphical abstract: Image 1 Highlights: Venom composition differs between Viperidae and Elapidae, Colubridae was not statistically different from either family. Viperidae crude venom was an effective antibacterial, Elapidae and Colubridae crude venoms were not effective overall. Viperidae and Elapidae crude venoms were effective antiparasitics overall, Colubridae crude venom was ineffective. Isolated venom proteins from Viperidae and Elapidae were effective antimicrobial components. There was a high prevalence of snake species with antimicrobial venom, especially within the Viperidae.